2022
DOI: 10.1136/bmjqs-2022-014695
|View full text |Cite
|
Sign up to set email alerts
|

How do hospital inpatients conceptualise patient safety? A qualitative interview study using constructivist grounded theory

Abstract: BackgroundEfforts to involve patients in patient safety continue to revolve around professionally derived notions of minimising clinical risk, yet evidence suggests that patients hold perspectives on patient safety that are distinct from clinicians and academics. This study aims to understand how hospital inpatients across three different specialties conceptualise patient safety and develop a conceptual model that reflects their perspectives.MethodsA qualitative semi-structured interview study was conducted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 69 publications
(96 reference statements)
1
34
0
Order By: Relevance
“…To promote PFE in patient safety, it is important to first understand the patient's unique preferences and care needs (Sahlström et al., 2019). Because some evidence suggests that patients hold perspectives on patient safety distinct from those of HCPs and that patients' sense of safety is formed through a series of care experiences (Barrow et al., 2022). Patient advocate, a novel stakeholder for patients, can also provide assistance to patients in many aspects of health care, making it slightly less complicated (Cho et al., 2022; Lara & Salberg, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To promote PFE in patient safety, it is important to first understand the patient's unique preferences and care needs (Sahlström et al., 2019). Because some evidence suggests that patients hold perspectives on patient safety distinct from those of HCPs and that patients' sense of safety is formed through a series of care experiences (Barrow et al., 2022). Patient advocate, a novel stakeholder for patients, can also provide assistance to patients in many aspects of health care, making it slightly less complicated (Cho et al., 2022; Lara & Salberg, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…partners are rich sources to guide learning and improvements in care and workflow processes [1][2][3][4][5][6][7][8] by increasing awareness of potential safety risks and reducing adverse events. 1,5,[8][9][10] Patients and care partners offer unique perspectives to safety as they often identify types of safety risks, events, and outcomes that differ from those identified by health care professionals.…”
mentioning
confidence: 99%
“…[11][12][13][14] Despite efforts, leveraging and learning from patients' and care partners' safety perspectives and experiences remain underutilized 1 for many reasons, including a failure to value and pay attention to their insights. This contributes to perpetuating a narrow understanding of safety, which is defined solely as the absence of harm, 4,5,15 thereby limiting safety conversations and improvements to care. Therefore, the purpose of this study was to gain a broader insight into how patients and care partners perceive and experience safety.…”
mentioning
confidence: 99%
“…3 In this issue, Archer et al contribute to this body of work. 4 The authors explored patients' conceptualisation of safety across three UK teaching hospital inpatient specialty wards in a qualitative interview study with a purposive sample of 24 English-speaking patients, 8 each from gerontology (medicine for the elderly), elective surgery and maternity (postnatal) wards. The authors found that patients in their study conceptualise safety as 'feeling safe' rather than 'being safe', and present a model of actions (performed, received, shared and observed) at the levels of self (patient), staff, family and friends, and the organisation that contribute to patients' 'feeling safe'.…”
mentioning
confidence: 99%
“…A growing body of research on patients’ and families’ understanding and conceptualisation of patient safety1 2 begs the question of how and why we, in healthcare and the field of patient safety and quality, conceptualise patient safety as a domain separate from patient-centredness and patient experience 3. In this issue, Archer et al contribute to this body of work 4. The authors explored patients’ conceptualisation of safety across three UK teaching hospital inpatient specialty wards in a qualitative interview study with a purposive sample of 24 English-speaking patients, 8 each from gerontology (medicine for the elderly), elective surgery and maternity (postnatal) wards.…”
mentioning
confidence: 99%